THE USE OF TEST-DAY MILK YIELD AND LAMBS WEIGHT FOR PREDICTION OF SOME PRODUCTIVE TRAITS IN AWASSI SHEEP - Muthanna F. A. Al-Juwari, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was included 155 records of Awassi ewes and 199 records of lambs born during two seasons (2011-2012), belonging to the College of Agriculture and Forestry, Mosul University. The effect of year was highly significant on all traits except for weight gain from weaning to 180 days (GW180d). Age of dam was significantly affected daily milk yield (DMY), birth weight (BW), weaning weight (WW) and gain from birth to weaning (GBW). Type of birth had significant  effect on DMY, BW,WW and weight at 180 days. The effect of lamb sex on WW, GBW was significant. Significant correlations coefficient were observed between DMY and total milk yield (TMY), months weight of lambs, GBW and GB180d being ranged from 0.46 to 0.99 and -0.44 to 0.99 respectively. The R2 values of prediction equations were high and ranged between 0.81 to 0.99 to predict TMY, and 0.97 to predict lamb weight at 180 days.